Crime and Victimhood in a Globalized World Order - Del Re E.; Shekhawat S. (Rivista di Criminologia, Vittimologia e Sicurezza, 2018)
Globalization has imposed a re-definition of crime – from slavery to corruption, to terrorism and other. Is it possible to elaborate a transversal and conventionally shared approach in the globalized society that allows all relevant actors to interpret contemporary criminal behavior correctly and act accordingly especially in relation to new conceptualization of victim? The Authors try to answer this crucial question raising issues such as the role of single countries as well as international organizations in defining global legislative frameworks and shared values. A strong anti-globalization wave that has emerged as a reaction to recent events such as migrations, asymmetric conflicts and other, is imposing a serious re-consideration of the existing structures, procedures and strategies. Are the current strategies, toolkits, approaches of legislators able to provide the necessary responses to the raising and pressing demands of recognition of local communities and at the same time to the need to maintain an equilibrium at global level? Through references to case studies such as migrants and refugees border crossing, examined from both global and local perspectives, the Authors intend to provide inputs for an innovative approach to reframing this phenomenon in a changing global order.